MANUSIA DAN TIPOLOGI MANUSIA DALAM PERSPEKTIF PSIKOLOGI ISLAM - afifa, Afifa Satrianis (JURNAL ISLAMIKA, 2025)
Humans are the most perfect creatures with their minds and hearts. However, from the perspective of dialectical materialism, humans are biological and economic creatures. In Islamic psychology, humans are placed as creatures created by Allah, but western psychology views humans as real creatures in the world or simply as the course of life. According to Islamic psychology, humans are considered to be a creation of Allah SWT which resembles a body simultaneously accompanied by a spirit. This research uses a type of research with literature or library research (library research). With sources from reading materials used in research that have been carried out by other people and have been published in the form of books, journals or articles so that they can be accessed via the internet or libraries. Basically, nature is found in the human psychophysical system and can be expressed in the form of behavior. Since the beginning of human creation, a unique initial image has been formed, even though the behavior is different, the nature of the human body is the same. Human typology from an Islamic perspective has been mentioned in the Koran. There are humans who are classified as good or not good, so based on this assessment humans can choose how their character should live their life Keywords: Humans, Typology, Perspective, Islamic Psychology